"Honour"-based violence in a British South Asian community. Issue 1 (15th December 2017) - Khan, Roxanne; Saleem, Shamam; Lowe, Michelle
Abstract : Purpose: The purpose of this paper is to explore attitudes towards, and victimisation experiences of, "honour"-based violence (HBV) in a reportedly vulnerable population in the UK. Design/methodology/approach: A convenience sample of 216 participants were recruited from a local community in England; the majority were young (mean age=21.93), Indian or Pakistani (85 per cent), Muslim (96 per cent), females (67 per cent). Findings: Although gender differences were found for attitudes towards one aspect of HBV (namely, forced marriage), these were not significant. While HBV victimisation affected only a small proportion of this sample, when it was reported, the effects were serious and included anxiety, attempted suicides and running away from home. This highlights the need to identify and safeguard vulnerable groups without stigmatising whole communities. Originality/value: These findings contribute to the scarce literature available on HBV in British communities, and highlight a need for culturally aware emergency and health service provision.